2015
DOI: 10.1007/s40279-015-0305-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Quality in Aging: a Multi-Dimensional Approach to Muscle Functioning with Applications for Treatment

Abstract: Aging is often accompanied by declines in physical functioning which impedes older adults' quality of life, sense of independence, and ability to perform daily tasks. Age-related decreases in skeletal muscle quantity, termed sarcopenia, have traditionally been blamed for these physical decrements. However, recent evidence suggests that the quality of muscle tissue may be more functionally relevant than its quantity. 'Muscle quality' has been emerging as a means to elucidate and describe the intricate intramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(199 citation statements)
references
References 271 publications
(347 reference statements)
4
183
1
11
Order By: Relevance
“…In elderly patients, it is demonstrated that muscle waste has to progress to a point below 30% of the mean of young adults before decrease in functional abilities are observed 21, 38. It has also been shown that physical performance is not solely dependent on muscle mass but also muscle strength 22, 39. Muscle strength, in turn, is reported to be independently associated with muscle radiodensity,40 and in accordance with our findings, greater muscular fat infiltration is found to increase the risk of immobility in older men and women 41…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In elderly patients, it is demonstrated that muscle waste has to progress to a point below 30% of the mean of young adults before decrease in functional abilities are observed 21, 38. It has also been shown that physical performance is not solely dependent on muscle mass but also muscle strength 22, 39. Muscle strength, in turn, is reported to be independently associated with muscle radiodensity,40 and in accordance with our findings, greater muscular fat infiltration is found to increase the risk of immobility in older men and women 41…”
Section: Discussionmentioning
confidence: 99%
“…The significant association between SMD and dyspnoea may support this assumption. As documented in geriatric patients, elevated fat content in the skeletal muscle may affect muscle strength more than plain muscle waste 21, 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, physiological assessments have primarily utilized skeletal muscle mass as a primary outcome metric for improving function in aged populations, yet results continue to be equivocal. More recently, muscle quality, defined as skeletal muscle performance per unit muscle mass, has been suggested and supported by data from basic, applied, and epidemiological research as being a more specific and sensitive outcome metric with respect to aging (and with respect to exercise training as well) [9,59,60].…”
Section: Musculoskeletal Disorders (Msds): Dynapenia Sarcopenia Andmentioning
confidence: 99%
“…It is chronic resistance exercise loading, or training, that is unique in promoting restoration or improvements in skeletal muscle performance (i.e., strength, work capacity, fatigue resistance, etc.) and skeletal muscle mass [83,84], as evidence for these findings exist in both human [57,71,83] and animal studies [66]; yet, little evidence exists for improving skeletal muscle quality in various populations, including aged populations [7,59]. There are numerous human studies that have suggested that resistance exercise training is beneficial in countering distinct components of musculoskeletal health and aging [71,83,84]; however, no translational study has shown that resistance exercise training can restore musculoskeletal health with aging to youthful states entirely.…”
Section: Efficacy Of Ssc Rtet In Restoring the Youthful Phenotypementioning
confidence: 99%